What difference do standards make to educating teachers? - Révai, Nóra (2018)
This paper reviews evidence on the interplay between professional standards for teachers, the content of teacher education and educational sciences, and provides three case studies to illustrate these interactions from Estonia, Australia and Singapore. In particular, it investigates what aligning teacher education programmes to standards really mean; and what conception of educational sciences is reflected in the standards and the curriculum. Analyses suggest that alignment, as an explicit, direct and consistent correspondence, is difficult to achieve, in part due to different conceptualisations of professional knowledge. However, this paper argues that the main value of standards as policy tools lies in their capacity to create mutual dialogue between different artefacts (standards’ requirements, curriculum, course descriptions, accreditation standards, etc.), as well as among stakeholders. Regularly renegotiating the standards as a result of such dialogue and reflections should be a crucial part of the policy process.